ANALISIS PENGARUH PELATIHAN, PROMOSI, DAN KEPUASAN TERHADAP KINERJA PERAWAT DI RUMAH SAKIT PERMATA MEDIKA SEMARANG (Students' Journal of Economic and Management, 2014)
This research study that tested the influence of training, promotion and job satisfaction of nurses in nurse’s performance in Permata Medika Hospital Semarang.This research has been fully tested on the respondents who work in the hospital as a nurse in Permata Medika Hospital Semarang, and hypothesis test using multiple regression test with the SPSS statistical tests.This research result explain that training, promotion and job satisfaction to employment and significant positive impact on the nurse’s performance. A variable whose most high influences the nurse’s performance is promotion based having the highest value on testing the regression coefficient.Keywords: training, promotion, and nurse’s job satisfaction